2019
DOI: 10.1287/msom.2018.0720
|View full text |Cite
|
Sign up to set email alerts
|

Selling a Product Line Through a Retailer When Demand Is Stochastic: Analysis of Price-Only Contracts

Abstract: To expand sales, many manufacturers try to develop and sell product lines. Frequently, however, the operations of distributing a product line creates tension between manufacturers and retailers as they do not necessarily agree on which product versions included in the product line should be sold to consumers. To mitigate this tension, previous literature has shown that if a manufacturer (he) wants to sell his product line through a retailer (she) who faces deterministic demand, then he needs to adjust his prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Throughout this study, we follow the terminology used in Netessine and Taylor (2007) and Chen et al (2013), for example, in which length refers to the quality difference between the highest and lowest products. This terminology varies somewhat across product-line papers, with some, e.g., Dong et al (2018), using length to refer to the number of products (size in our terminology). 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout this study, we follow the terminology used in Netessine and Taylor (2007) and Chen et al (2013), for example, in which length refers to the quality difference between the highest and lowest products. This terminology varies somewhat across product-line papers, with some, e.g., Dong et al (2018), using length to refer to the number of products (size in our terminology). 5…”
Section: Discussionmentioning
confidence: 99%
“…In a two‐product setting with demand uncertainty, Dong et al. (2018) examine the impact of push and pull contracts on the manufacturer’s assortment choice, that is, whether to offer one or two products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Shen et al (2020) studied the optimal product differentiation strategy of green and non‐green products with quality differences in the supply chain and found that a single product strategy may be more advantageous for enterprises than a differentiated product strategy. Some scholars consider product differentiation strategies under different situations, such as product differentiation strategies with random demand considered (Dong et al, 2019), product differentiation strategies with social impact considered under platform economics (Ji et al, 2022), product differentiation strategies with price reference effects considered (Yan et al, 2022), and product differentiation strategies with environmental responsibility behavior considered (Xiao & Choi, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To satisfy the various demands of customers and gain a competitive advantage, manufacturers often take a product variety strategy by producing multiple variants of the same product (Ramdas, 2003; Xiao and Shi, 2016; Dong et al., 2019). In the electronics industry, for example, considering different usage scenarios of customers, manufacturers such as Hewlett‐Packard and Samsung produce and sell monitors in various sizes, colors, or designs.…”
Section: Introductionmentioning
confidence: 99%